UJI ATRAKTAN PADA EKSTRAK PURUN TIKUS (Eleocharis dulcis) SEBAGAI PERANGKAP HAMA PENGGEREK BATANG PADI PUTIH - Kholifatu Rosyidah; Zacky Insan; Dahlena Ariyani (Lambung Mangkurat University-Indonesia, 2021)
Purun tikus (Eleocharis dulcis) are wild plants found on swamp land which are quite abundant in South Kalimantan. This research was conducted to find out the most active extract from Chinese water chestnut as an attractant of white rice stem borer (Scirpophaga innotata). Purun tikus were made into extracts using the stepwise extraction method using n-hexane, ethyl acetate, and methanol, with yields of 0.74%, 0.81%, and 7.58%, respectively. The results of the attractant test on purun tikus extract showed that the extract of n-hexane purun tikus was the most active extract as an attractant in white rice stem borer (Scirpophaga innotata). The results of the analysis using GC-MS showed that the extract of n-hexane purun tikus contained several compounds, namely 2-methyltetrahydrofuran, isopulegol, citronellal, citronellyl acetate, βcitronellol, Z-citral, 1-bromo-3,7-dimethyl-2,6-octadiene, citral, linalyl acetate, trans-caryophyllen, trans-phytol, verticellol.